Paraganglioma – Predictors factors of major aggressivity - Teixeira, Carina (2024)
Paragangliomas are rare neuroendocrine tumors whose clinic and presentation depend on secretory profile, size, and location. About 40% of paragangliomas are associated with genetic syndromes with the succinate dehydrogenase enzyme complex (SDH) mutation being the most frequent. Mutation in SDHB is associated with a worse prognosis and increased risk of metastatic disease. We present a clinical case of a 45-year-old man, with a germline mutation in the SDHB gene, who initially underwent excision of paraganglioma with 10 cm that recurred with disseminated disease. He underwent several systemic treatments with some response but unfortunately died in the context of oncologic disease. Regarding this case, we review some predictors of poor prognosis.